1974
DOI: 10.1159/000468119
|View full text |Cite
|
Sign up to set email alerts
|

Klinisch-neuroleptische Untersuchung des N-[(l-Äthyl-pyrrolidin-2-yl)-methyl]-2-methoxy-5-sulfamoyl- Benzamid-Neuroleptikums Sulpirid (Dogmatil®) an akut erkrankten Schizophrenen

Abstract: The paper reports on 26 acute, first time or repeatedly diseased schizophrenic patients, who were treated by Sulpiride in a psychiatric ward. The method used was a variant of the single-blind technique of administration and evaluation, the basic conception being that of the ‘neuroleptic threshold’ of Haase. The substance proved to be an intermediary drug between feeble and middle-potent neuroleptics. In doses about 200 mg/ day, it showed a mood-clearing and stimulating effect. The average dosis necessary to re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

1976
1976
2000
2000

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…Thus, our PCP model could be used as a new model of the negative symptoms. Haase et al (1974) reported that chronic schizophrenic patients given sulpiride, a selective dopamine 2 receptor antagonist, showed an elation of mood and clearing of negative signs. Elizur and Davidson (1975) also found sulpiride is effective in improving the autistic state of schizophrenic patients.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, our PCP model could be used as a new model of the negative symptoms. Haase et al (1974) reported that chronic schizophrenic patients given sulpiride, a selective dopamine 2 receptor antagonist, showed an elation of mood and clearing of negative signs. Elizur and Davidson (1975) also found sulpiride is effective in improving the autistic state of schizophrenic patients.…”
Section: Discussionmentioning
confidence: 99%
“…The antipsychotic action of these agents, however, is possibly not connected with the impairment of the nigrostriatal dopamine transmission. In fact, sulpiride (Borenstein, Champion & others, 1969;Haase, Florn & Ulrich, 1974;Tagliamonte, de Montis & others, 1975), clozapine (Burki, Eichenberger & others, 1975) and thioridazine (Cole & Clyde, 1961), which are claimed to display antipyschotic properties (1) do not cause marked extrapyramidal side effects in either man or animals and (2) are by far less potent than classical neuroleptic drugs (e.g. chlorpromazine and haloperidol) in enhancing striatal dopamine turnover which is thought to be triggered by the blockade of dopamine receptors (vide infra).…”
mentioning
confidence: 99%
“…However, in a previous study we found 800 mg of sulpiride to be effective in the treatment of psychotic patients (20). Moreover, Haase et al (12) found an antipsychotic effect with 600 mg of sulpiride. Chlorpromazine was selected as reference.…”
Section: Introductionmentioning
confidence: 84%
“…This in turn may indicate a lower risk of inducing tardive dyskinesia. The drug has also been claimed to be especially effective in autistic patients (12,13,10). Several double-blind comparisons with conventional neuroleptics like chlorpromazine, haloperidol and trifluoperazine indicate that sulpiride has antipsychotic effect in schizophrenic patients (14,15,16,17,18,19).…”
Section: Introductionmentioning
confidence: 99%